Liquid Crystal Based Binding Assay for Detecting HIV-1 Surface Glycoprotein - Abbasi, Amna Didar; Hussain, Zakir; Liaqat, Usman; Arif, Dooa; Yang, Kun-Lin (Frontiers in Chemistry, 2021)
Surface protein gp-120 of HIV-1 virus plays an important role in the infection of HIV-1, but detection of gp-120 during the early stage of infection is very difficult. Herein, we report a binding bioassay based on an RNA aptamer B40t77, which binds specifically to gp-120. The bioassay is built upon a hydrophobic glass slide with surface immobilized gp-120. When the glass surface is incubated in a solution containing B40t77, the aptamer is able to bind to gp-120 specifically and remove it from the surface after a short incubation time of 30 min. The result of the binding event can be amplified by using liquid crystal (LC) into optical signals in the final step. By using this bioassay, we are able to detect as low as 1µg/ml of gp-120 with high specificity within 30 min. No response is obtained when gp-120 is replaced by other protein such as bovine serum albumin (BSA). This is the first qualitative bioassay which provides a simple way for the detection of gp-120 with the naked eye. The assay is robust, low-cost and does not require additional labeling. Thus, the bioassay is potentially useful for the early detection of HIV-1 in resources-limited regions.